2016
DOI: 10.1186/s12985-016-0599-y
|View full text |Cite
|
Sign up to set email alerts
|

Codon optimization of antigen coding sequences improves the immune potential of DNA vaccines against avian influenza virus H5N1 in mice and chickens

Abstract: BackgroundHighly pathogenic avian influenza viruses are a serious threat to domestic poultry and can be a source of new human pandemic and annual influenza strains. Vaccination is the main strategy of protection against influenza, thus new generation vaccines, including DNA vaccines, are needed. One promising approach for enhancing the immunogenicity of a DNA vaccine is to maximize its expression in the immunized host.MethodsThe immunogenicity of three variants of a DNA vaccine encoding hemagglutinin (HA) from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(32 citation statements)
references
References 35 publications
0
32
0
Order By: Relevance
“…Comparing the codon usage in E. coli, we found many rare codons in the wild DWV structural protein genes, and CAI values of the three target genes were only approximately 0.2; this likely results in lower expression yields-even expression failure -in E. coli. Codon optimization can improve protein production via optimization of translation elongation, and previous reports have shown that a codon-optimization strategy can improve the expression level of genes in many species (Chu et al, 2018;Hu et al, 2019;Nieuwkoop et al, 2019;Sun et al, 2017). In this study, the rare codons of DWV VP1, VP2, and VP3 were replaced with the most highly preferred codons, and the GC content was changed to approximately 70%.…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…Comparing the codon usage in E. coli, we found many rare codons in the wild DWV structural protein genes, and CAI values of the three target genes were only approximately 0.2; this likely results in lower expression yields-even expression failure -in E. coli. Codon optimization can improve protein production via optimization of translation elongation, and previous reports have shown that a codon-optimization strategy can improve the expression level of genes in many species (Chu et al, 2018;Hu et al, 2019;Nieuwkoop et al, 2019;Sun et al, 2017). In this study, the rare codons of DWV VP1, VP2, and VP3 were replaced with the most highly preferred codons, and the GC content was changed to approximately 70%.…”
Section: Discussionmentioning
confidence: 91%
“…Research has indicated that structural proteins of the virus not only play an important role in viral invasion and replication but also have excellent immunogenicity and that they are frequently selected as candidates for the development of therapeutic antibodies (Huo et al, 2018;Li et al, 2014;Stachyra et al, 2016;Wang et al, 2017). Compared with vertebrate immune systems, honey bee immune pathways lack acquired immunity (Bull et al, 2012) and cannot directly generate specific antibodies in response to an antigen.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…During the plasmid design, low-frequency eukaryotic codons in the foreign DNA backbone are identified and replaced for high-frequency codons, while still maintaining their respective coded amino acids [130][131][132]. There has been recent progress in terms of enhancing the immunogenicity in mice and chicken primed with such codon-optimized DNA vaccines [133][134][135].…”
Section: Codon Optimizationmentioning
confidence: 99%
“…HI tests were performed as described previously (Stachyra et al, 2014;Stachyra et al, 2016) Antibodies. IgY 745 -anty-H5 HA (H5N1) polyclonal IgY was purified in our laboratory from eggs collected from laying hens immunized with DNA vaccine based on pCI vector with cloned cDNA sequence encoding 1-568 aa of HA from A/swan/Poland/305-135V08/2006 (H5N1) (Stachyra et al, 2014).…”
Section: Methodsmentioning
confidence: 99%